Persepsi Guru Pamong Terhadap Profesional Mahasiswa Praktek Lapangan Kependidikan (Universitas PGRI Sumatera Barat, 2017)
This study aims to find out how the perception of teachers tutor toprofessional competence of students Field Training Practices. The sampling technique uses total sampling. Data collection techniques are questionnaires. The type of questionnaire used is a closed questionnaire type with a checklist form. Data analysis technique used is descriptive statistical analysis. Based on the research data, it is known that teachers 'perceptions of the competence of Field Training Practices students in mastering the learning materials, managing the learning process, assessing the students' learning achievement, managing the class, managing the teaching and learning interaction including the excellent category, and using media including good categoryThis study aims to find out how the perception of teachers tutor toprofessional competence of students Field Training Practices. The sampling technique uses total sampling. Data collection techniques are questionnaires. The type of questionnaire used is a closed questionnaire type with a checklist form. Data analysis technique used is descriptive statistical analysis. Based on the research data, it is known that teachers 'perceptions of the competence of Field Training Practices students in mastering the learning materials, managing the learning process, assessing the students' learning achievement, managing the class, managing the teaching and learning interaction including the excellent category, and using media including good category